Principles and processes of interactive design - Steane, Jamie, ....- (London : Bloomsbury Academic, 2014)
"The Principles and Processes of Interactive Design is for new designers from across the design and media disciplines who need to learn about the fundamental principles and processes behind designing for digital media. This book is intended as both a primer and companion guide, that covers the design essentials from a digital perspective: user-based design research and development, digital colour and image, typography and hypertextuality, working with digital formats, screen-based grids and layouts, and storyboards and system mapping, as well as offering general guidance on how to present your ideas. Featured contributors include: Moving brands;The Chase; Happy Cog; Red Bee; BBC iPlayer; Imaginary Forces; and Bibliotheque Design"--
Machine generated contents note: -- Introduction Chapter 1: Research and developmentUnderstanding the brief; Market research; User research; Visual research; Conceptual thinking; Feedback and user testing; Industry perspective: Moving Brands; Workshop I - Connected life.Chapter 2: Colour and image: Colour meaning and psychology; Colour in technical detail; Working with colour; Using colour systems; Decoding images; Creating images; Using Photo Libraries; Preparing Images; Case Study - The Chase; Workshop II: 'Taste and After-Taste'Chapter 3: Typography and hypertextuality: Fundamentals; Classification and selection; Legibility and readability; Uses of type on screen; Using type as image; Web publishing and hypertext; User controlled typography; Using type on small devices; Case Study - Happy Cog - Fontshop; Workshop III: 'Face to Face'.Chapter 4: Components and Formats: Television broadcast standards and sizes; TV graphics components; Standard web page sizes; Web banners sizes and formats; Mobile screen sizes; File formats; Case Study - Red Bee; Workshop IV: 'One message, many formats'.Chapter 5: Grids and Screen Layouts: What are grids; Principles of Composition; Balance and contrast; Size and scale; Hierarchy; Repetition and sequencing; Working in planes and 3D space; Working with safety areas; Designing graphic user interfaces (GUIs); Creating wireframes; Using metaphors; Web fixed and liquid layouts; Global and local navigation; Case Study - BBC IPlayerWorkshop V: 'It's all news to me'.Chapter 6: Storyboards and system mapping: Film language basics; Storyboarding; Working with sound; Creating animatics; Paper prototyping; System mapping Case Study - Imaginary Forces; Workshop VI: 'BE TV'.Chapter 7: Presenting your work: Digital presentations; Physical presentations; Presentation tips and techniques; Creating digital and analogue portfolios; Case Study - Bibliotheque Design; Workshop VII: 'Branding You'.ConclusionGlossaryBibliographyUseful ResourcesIndex.
Includes bibliographical references and index.
Keywords: Commercial art -- Data processing; Graphic arts -- Data processing; Digital media -- Design; Design -- General